2019
DOI: 10.1002/jcb.28376
|View full text |Cite
|
Sign up to set email alerts
|

Adipose mesenchymal stem cell‐derived exosomes promote cell proliferation, migration, and inhibit cell apoptosis via Wnt/β‐catenin signaling in cutaneous wound healing

Abstract: Cutaneous wounds, a type of soft tissue injury, are difficult to heal in aging. Differentiation, migration, proliferation, and apoptosis of skin cells are identified as key factors during wound healing processes. Mesenchymal stem cells have been documented as possible candidates for wound healing treatment because their use could augment the regenerative capacity of many tissues.However, the effects of exosomes derived from adipose-derived stem cell (ADSC-exos) on cutaneous wound healing remain to be carefully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(153 citation statements)
references
References 29 publications
7
134
0
Order By: Relevance
“…The size of exosomes can be identified by TEM and NTA, and proteins such as CD63, CD81, TSG101, and HSP70, which are usually rich in exosomes, can be identified by western blot [15]. Numerous recent studies [38][39][40] showed that mesenchymal stem cell-derived exosomes (MSC-Exo) promoted the repair of tissue damage, leading to great progress in wound repair. MSC-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of exosomes can be identified by TEM and NTA, and proteins such as CD63, CD81, TSG101, and HSP70, which are usually rich in exosomes, can be identified by western blot [15]. Numerous recent studies [38][39][40] showed that mesenchymal stem cell-derived exosomes (MSC-Exo) promoted the repair of tissue damage, leading to great progress in wound repair. MSC-…”
Section: Discussionmentioning
confidence: 99%
“…Exo were also shown to induce the proliferation and migration of vascular endothelial cells, promote angiogenesis, and reduce apoptosis of endothelial cells, indicating important roles in injury repair and vascularization [10,39]. In the current study, we therefore applied ADSC-Exo to artificial dermal prefabricated flaps to overcome the issue of insufficient vascularization.…”
Section: Stem Cells Internationalmentioning
confidence: 98%
“…Studies have shown that ASC-exos played a positive role in cutaneous wound healing by means of acting on HDFs and HaCaTs and other main target cells through various signal channels ( Figure 1C; Qiu et al, 2020). Ma et al (2019) exposed HaCaTs to hydrogen peroxide (H 2 O 2 ) for establishing a skin lesion model, discovering that ASC-exos could foster HaCaTs proliferation, migration, and inhibit apoptosis through Wnt/β-catenin signaling pathway. Likewise, He et al (2020) also confirmed that MALAT1-containing ASC-exos improved wound healing by targeting miR-124 and activating Wnt/β-catenin pathway.…”
Section: Asc-exos In Wound and Scarmentioning
confidence: 99%
“…On the other hand, levels of ROS and inflammatory cytokines were significantly decreased by treatment with ASC-Exos. Using HaCaT cells exposed to hydrogen peroxide (H 2 O 2 ) for the establishment of a skin lesion model, Ma et al [83] explored the effects of Exos derived from human facial adipose tissue on cell proliferation assessed by the cell counting kit (CCK)-8 assay, and the migration rate analyzed with standard scratch wound healing and transwell assays. Exos were extracted from 24 h ASC-CM using a commercial exosome isolation reagent, characterized with TEM for the morphology and size (30-100 nm).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…induced apoptosis levels [83]. ASC: adipose tissue-derived stem cell; HMEC: human mammary epithelial cell; HDF: human dermal fibroblast; HUVEC: human umbilical vein endothelial cell; Akt: protein kinase B; PI3K: phosphoinositide 3-kinase; ERK: extracellular signal-regulated kinase; HaCaT: spontaneously immortalized human keratinocyte cell line.…”
mentioning
confidence: 99%